2020
DOI: 10.1177/1099636220905778
|View full text |Cite
|
Sign up to set email alerts
|

On stability and damage behavior of asymmetric sandwich panels under uniaxial compression

Abstract: In practical applications, asymmetric sandwich panels with tapered and junction regions are frequently used. Under uniaxial compressions, asymmetric sandwich panels are collapsed with complex failure mechanism, and its mechanical behaviour is affected by tapered regions. For structure safety consideration, it is necessary to systematically investigate the stability and damage behavior of full-scaled asymmetric sandwich panels under uniaxial compression experimentally and numerically. For comparison, symmetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…The sign change in slope can serve as an indicator of buckling. 17 Initially, the strains in WFS and SFS exhibit a linear increase with the applied load. After buckling, the strain-load curves in the SFS become non-linear.…”
Section: Experimental Results and Numerical Predictionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sign change in slope can serve as an indicator of buckling. 17 Initially, the strains in WFS and SFS exhibit a linear increase with the applied load. After buckling, the strain-load curves in the SFS become non-linear.…”
Section: Experimental Results and Numerical Predictionsmentioning
confidence: 99%
“…When composite sandwich structures are subjected to compression loads, instability becomes one of the failure modes. Our preliminary research 17 showed that ASPs could still bear significant loads after buckling. The ultimate failure of ASPs was resulted by the combined effects of buckling, core shear, skin delamination, skin/core debonding, and stress concentration at the junction region.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…2 Investigations of tapered sandwich structures have attracted researchers' interests in the past. [3][4][5][6][7][8][9] A review of composite sandwich structures for aeronautical applications is presented by Castanie et al 10 A variety of nacelle composite structures include sandwich panels that contain closeout design configurations. A closeout (ramp) is formed at the region where a sandwich panel transitions to solid laminates.…”
Section: Introductionmentioning
confidence: 99%